2022
DOI: 10.1097/mpg.0000000000003657
|View full text |Cite
|
Sign up to set email alerts
|

Nutri‐Score

Abstract: Reducing the burden of noncommunicable diseases (NCDs) is one of the top priorities of public health policies worldwide. One of the recognized means of achieving this objective is to improve the diet quality. The Nutri-Score (N-S) is a [five-color—A, B, C, D, E letters] front-of-pack labeling logo intended to help consumers quickly identify the healthier prepackaged foods within a food category. Available studies have shown that the N-S is an efficient tool to achieve this aim in terms of consumers’ awareness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…The Nutri-Score system has been analysed in many studies. While many of these studies have shown that the system fits in with healthy eating and public health recommendations [ 12 ], as well as in helping to make healthier dietary choices and improving the health of the population [ 12 , 13 , 14 , 15 ], the scientific community has also highlighted the flaws and systemic shortcomings of this algorithm, or pointed to the lack of clear and reliable evidence of its positive impact on consumers’ dietary choices [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Nutri-Score system has been analysed in many studies. While many of these studies have shown that the system fits in with healthy eating and public health recommendations [ 12 ], as well as in helping to make healthier dietary choices and improving the health of the population [ 12 , 13 , 14 , 15 ], the scientific community has also highlighted the flaws and systemic shortcomings of this algorithm, or pointed to the lack of clear and reliable evidence of its positive impact on consumers’ dietary choices [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%